Vitiligo and Hashimoto's thyroiditis: Autoimmune diseases linked by clinical presentation, biochemical commonality, and autoimmune/oxidative stress-mediated toxicity pathogenesis. (July 2019) - Li, Dongmei; Liang, Guanzhao; Calderone, Richard; Bellanti, Joseph A.
Abstract: Vitiligo (VL) is a chronic autoimmune pigmentation disorder characterized by destruction of melanocytes. The condition is associated with several other autoimmune diseases, but autoimmune thyroid diseases, especially Hashimoto's thyroiditis (HT), is the most prevalent organ-specific autoimmune disease with a co-morbidity up to 34%. Among the many hypotheses that have been proposed for the pathogenesis of both diseases, autoimmunity and oxidative stress-mediated toxicity in melanocytes or thyrocytes, respectively, have been the most widely accepted – with autoimmunity being the presumed consequence of oxidative stress-mediated toxicity. However, the predominant etiologic basis for impairment of redox balance has rarely been studied. The two autoimmune diseases are not only linked by a concordance of clinical presentations and an autoimmune/oxidative stress-mediated toxicity pathogenesis but also by an apparent biochemical commonality. The target molecules produced in the thyroid and skin, i.e., thyroxine and melanin, respectively, are derived from the same primordial parent molecule, tyrosine. On the basis of these similarities between Hashimoto's thyroiditis and vitiligo, specifically with respect to the activation of oxidative stress, we propose a novel hypothesis accounting for the destruction of melanocytes or thyrocytes in VL and AT. We suggest a new therapeutic regimen of quinone derivatives to combat ROS-induced autoimmunity resulting from this common biochemical etiologic error.